2002
DOI: 10.1046/j.1526-4610.2002.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Automatic Thoughts, Alexithymia, and Assertiveness in Patients With Tension‐type Headache

Abstract: These findings suggested that persons with tension-type headache have high depression scores and also may have difficulty with expression of their emotions. Headache frequency appears to influence the likelihood of coexisting depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 31 publications
1
59
0
6
Order By: Relevance
“…Indeed, headaches have been associated with depression. 26,27 Individuals with medication overuse headaches were excluded because they could constitute a particular group that is difficult to treat and whose medication may have altered serotonin reuptake activity. Patients with a history of substance or alcohol abuse were excluded for the same reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, headaches have been associated with depression. 26,27 Individuals with medication overuse headaches were excluded because they could constitute a particular group that is difficult to treat and whose medication may have altered serotonin reuptake activity. Patients with a history of substance or alcohol abuse were excluded for the same reasons.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we investigated the relationship between pain location and anxiety, depression and alexithymia in strictly unilateral migraineurs. Alexithymia, substantially defined by difficulty in identifying and describing own feelings and by an externally oriented cognitive style [16], has been previously investigated in headache patients [17], in particular in those with chronic tension-type headache [18]. Recent data showed that alexithymia is more frequent in MO patients compared to healthy subjects [19].…”
Section: Discussionmentioning
confidence: 99%
“…Admite-se que doentes com CTTE apresentem sintomas de ansiedade mais intensos, enquanto aqueles com CTTC têm sintomas depressivos mais exuberantes 6,16,17 . Tanto a ansiedade quanto a depressão podem atuar em nível central como facilitadores das aferências dolorosas, participando desta forma da patogênese da dor (especialmente na CTTC) 16 .…”
Section: Discussionunclassified
“…Tanto a ansiedade quanto a depressão podem atuar em nível central como facilitadores das aferências dolorosas, participando desta forma da patogênese da dor (especialmente na CTTC) 16 .…”
Section: Discussionunclassified